2008
DOI: 10.4049/jimmunol.180.1.198
|View full text |Cite
|
Sign up to set email alerts
|

CD62L (L-Selectin) Down-Regulation Does Not Affect Memory T Cell Distribution but Failure to Shed Compromises Anti-Viral Immunity

Abstract: The down-regulation of CD62L that accompanies T lymphocyte activation is thought to redirect cells away from lymph nodes to sites of infection. In this study, CD62L was maintained on Ag-activated T cells and their distribution, and ability to clear pathogen from peripheral sites determined. CD62L was down-regulated on Ag-specific CD8 T cells in lungs of C57BL/6 mice but maintained in CD62L transgenic mice at day 8 after influenza infection. However, the numbers of influenza-specific CD8 T cells recruited were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
3
29
1
Order By: Relevance
“…Studies have shown that CD62L shedding plays an important role in T cell activation in the lymph nodes. Further, it is confirmed that although CD62L is present on memory T cells its shedding is not essential for the production of memory T cells or T cell immigration to the infection site, thus, the lack of shedding can affect the viral elimination effect [339].…”
Section: Cd62l Precursor Of Memory T Cellmentioning
confidence: 61%
See 4 more Smart Citations
“…Studies have shown that CD62L shedding plays an important role in T cell activation in the lymph nodes. Further, it is confirmed that although CD62L is present on memory T cells its shedding is not essential for the production of memory T cells or T cell immigration to the infection site, thus, the lack of shedding can affect the viral elimination effect [339].…”
Section: Cd62l Precursor Of Memory T Cellmentioning
confidence: 61%
“…It is also argued that this epitope also bears at least one B cell epitope (323)(324)(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339), however, there is only one study that has mentioned the presence of the B cell epitope [327]. In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
See 3 more Smart Citations